Ko hoku hala fononga ki he lea faka-Tonga: Examining Changing Linguistic Identity in Aotearoa NZ - Lufe, Talilupe (Auckland University of Technology, 2023)
Linguistic identity is an essential component of one’s holistic identity. This holds especially true for bi/multi-lingual people. Many scholars have studied linguistic identity and have found that through its various strands, it is the key to providing a sense of connection to other people through language. When I grew up as a New Zealand-born Tongan in the 1990s and 2000s, there was a decline in the Tongan language, with children abandoning the language and only adults who had been born in Tonga speaking it fluently. Most first-generation (in New Zealand) Tongan children grew up speaking only English, the dominant language and used it on a daily basis. There was little attention on sustaining, maintaining, and revitalising the Tongan language in Aotearoa. This autoethnographic study examines my changing linguistic identity as I acquired the Tongan language in Aotearoa. I investigated how my linguistic identity has been shaped over the course of my life. I performed narrative writing to describe my hala fononga ki he lea faka-Tonga in Aotearoa. In addition, I was curious as to whether and why I rejected the Tongan language as a child, as well as how my parents encouraged me to learn and speak Tongan. I was lotolotoua about which language to acquire and use, so I chose English over Tongan. Nonetheless, I was incidentally learning the Tongan language without my knowledge. If there had been as many Tongan language nest facilities in the area where I grew up as there are now, I might have learned the Tongan language as a young child. Over time, I became loto-fekumi because I wanted to learn more about the Tongan language to communicate with others, which led to some degree of autonomous language learning. Being surrounded by speakers of the Tongan language inspired me to learn and speak the language. This became the motivation for learning the Tongan language. I started to loto-feinga to learn Tongan so that I could communicate with other Tongan speakers. This is significant because it assists me in appreciating my koloa of the Tongan language and understanding my linguistic identity, which can support others in recognising their linguistic identity.